Implementasi Pengembangan Profesionalisme Guru Pendidikan Agama Islam di SMPIT Nurul Islam Tengaran - Muhammad Rofiq; Mukh Nursikin (Departement of Mathematics Education, 2023)
This study aims to examine the implementation of teacher professionalism development at SMPIT Nurul Islam Tengaran. This study uses a qualitative descriptive approach. The main sources in this study were PAI teachers, principals, other subject teachers, TU officers, and students. The findings in this study are about the implementation of teacher professionalism development at SMPIT Nurul Islam Tengaran, among others: 1) participating in the PAI subject teacher deliberations (MGMP) activities, 2) conducting comparative studies with other schools, 3) participating in Al-Qur'an reading training Qur'an (tahsin), 4) participate in the liqo' or halaqah tarbawiyah program, which is a program to foster one's religion so that he can become a person of character, and 5) participate in the program of tahfidz Al-Qur'an and memorization of hadith, which is a mandatory program from the Integrated Islamic School Level (JSIT).